X-ray cavities in TNG-Cluster: a direct comparison to observations - Prunier, Marine; Pillepich, Annalisa; Hlavacek-Larrondo, Julie; Nelson, Dylan (Monthly notices of the Royal Astronomical Society, 2025)
The TNG-Cluster magnetohydrodynamic cosmological simulations produce a diverse population of X-ray cavities in the intracluster medium (ICM) of simulated galaxy clusters. These arise from episodic, high velocity, kinetic energy injections from the central active supermassive black hole (AGN, SMBH). Here, we present the first comprehensive comparative analysis of X-ray cavities in TNG-Cluster with observational data. First, we select a volume-limited sample of 35 real clusters